Thermal-emission assessment of building ceilings from agro-industrial wastes - Joseph O Dirisu (Elsevier, 2022)
Most of the building ceiling tiles used today from studies, such as polyvinyl chloride (PVC) composite ceilings, cardboard, plywood, particleboard, are flame friendly. Except for asbestos, which is confirmed to emit asbestosis, cancer from asbestos; already warned by the Environmental Protection Agencies and other health standard organizations. Studies have shown inherent harmful elements associated with the use of PVC Ceiling composite, plant-based ceiling, and asbestos, which propagate noxious emission at the instance of fire; their widespread use is quite enormous. The noxious behaviour during an inferno is a representation of the elemental make-up of these ceiling materials. Moreover, their vulnerability due to emission and combustion threat call for alternative materials with eco-friendly constituents for building ceiling applications. Problems associated with these building ceilings during fire include noxious gaseous emissions; fuel for the flame from ignition from other roof frame structures; after flame effect of inhaling poisonous gasses against the recommended exposure limit of 35 ppm by the World Health Organization (WHO). Flame retardance is credited to asbestos. However, for other ceiling tiles, some of the challenges of high heat flux, high thermal conductivity, and combustibility tendencies, are still current issues. The undesirable side effects of using ceiling tiles have necessitated a replacement with suitable flame retardant and eco-friendly influences. This is made to bear by appropriate material selection and by employing industrial wastes and agricultural wastes coupled with suitable binders to solve flame propagation challenges. It is, therefore, necessary to develop a flame retardant ceiling composite that will solve the identified anomalies in the existing ceiling tiles in the market in building industries. The developed materials are tested for thermal and emission characteristics to ascertain their integrity by employing advanced test equipment. The result shows that there are low values in thermal conductivity of the developed building ceiling samples. Sample 2 has the lowest value compared to the developed and existing ceiling tiles, much < 0.0802 W/mK, which is a desirable property in ceiling application. Low thermal diffusivity is required to suppress flame propagation. This is exhibited by sample 1, with a value of 0.85 × 10−8 m2/s as the lowest amongst developed ceiling samples The result showed null and negligible SO2 detection for all samples. The three samples' time to attain pre-set temperature varies in the ascending order of sample 1 at 24 min, sample 3 at 37 min, and sample 2 at 42 min. Sample 3, 0.6Aldr0.34Cmt0.05G0.01OBS; Sample 2, 0.6Aldr0.32Cmt0.05G0.03OBS and sample 1, 0.6Aldr0.3Cmt0.05G0.05OBS are in the order in terms of safe emission characteristics while sample 2 ranks best in terms of flame retardancy.This study has established that the developed building ceiling composite material is flame retardant capable of preventing fire propagation, unlike the flammable polyvinyl chloride (PVC) ceiling composite. The developed building ceiling composite can minimize the emission of harmful elements in the make-up of the ceiling, as revealed in the results. The tiles are alternative to both noxious PVC and asbestos ceiling tiles. Oil beanstalk is a novel material introduced as a reinforcement to the developed composite. The manufacturing industries should explore materials with excellent eco-friendly flame retardant constituents to encourage sustainable building production.